2005
DOI: 10.1002/star.200500412
|View full text |Cite
|
Sign up to set email alerts
|

Gelatinisation Properties of Cassava Starch in the Presence of Salts, Acids and Oxidising Agents

Abstract: The effect of various cations, anions, acids and oxidising agents on the gelatinisation properties of cassava starch was studied and wide variation was observed in the pasting and swelling properties. Sodium chloride and sodium thiosulphate slightly lowered the peak viscosity of cassava starch with increase in concentration, whereas with sodium sulphite, calcium chloride and sodium hypochlorite, a more significant decrease in the viscosity and breakdown was observed. Ferrous sulphate, alum, aluminium chloride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 18 publications
7
37
0
3
Order By: Relevance
“…Comparable results have been found for rice starch 4 , and wheat starch granules 18 . For cassava starch, however, no significant change in peak viscosity was observed when the NaCl level increased from 0.05-2%, while it slightly increased at 2.5 and 5% NaCl 3 . Differing from cassava starch, PS molecule contains phosphate groups which would affect the viscosity by interacting with NaCl 19 .…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Comparable results have been found for rice starch 4 , and wheat starch granules 18 . For cassava starch, however, no significant change in peak viscosity was observed when the NaCl level increased from 0.05-2%, while it slightly increased at 2.5 and 5% NaCl 3 . Differing from cassava starch, PS molecule contains phosphate groups which would affect the viscosity by interacting with NaCl 19 .…”
Section: Resultsmentioning
confidence: 79%
“…Viscosity of corn starch could be increased with salt 2 . Peak viscosity of cassava starch could be promoted with 2.5-5% NaCl 3 . Rice starch with high content of amylopectin exhibits better swelling properties.…”
Section: Introductionmentioning
confidence: 99%
“…Fakat şişen nişasta granüllerinin sürekli ısıtılması ve karıştırılmasıyla nişasta süspansiyonunda kırılmalar oluşarak viskozitede azalma meydana gelir. Viskozite değeri minimum değere ulaşır (Jyothi et al, 2005). Oluşan bu azalma, yani pik viskozitesiyle, incelme sonrası viskozite arasındaki fark, HVT analizinde incelme viskozitesi olarak adlandırılır.…”
Section: Dpph Radikali Temizleme öZelliğiunclassified
“…Many studies have been curried out to investigate the effect of salts when it mixed with starch [7,21,[59][60][61][62][63][64] which reported that salts caused an elevation or depression of gelatinization temperature and gelatinization enthalpy, depending on the types of salt and their concentrations used. Researchers [7,21,59] have reported that NaCl and CaCl 2 combination at low concentrations, slightly increased the T p of sago starch but, when the concentrations increased further (up to ~2 M for NaCl and ~1 M for CaCl 2 ), these temperatures decreased.…”
Section: Thermal Behaviour Of Sago Starch-salts Mixturementioning
confidence: 99%